Mind Mapping Assisted Talking Stick Learning Model on Speaking Skills - Sastrawan, Putu Agus Putra; Sudana, Dewa Nyoman; Arini, Ni Wayan (Universitas Pendidikan Ganesha, 2020)
Low student speaking skills can result in a less active learning process. This research aimed to know the talking stick learning model's significant effect with mind mapping for speaking skills in fifth-grade students. This research was quasi-experimental research with used non-equivalent post-test only control group design. The population in this research was 125 students, and the sample of this research amounted to 45 students who were determined by a simple random sampling technique. Data on students speaking skills were collected using the non-test method in the form of assessment for work. Data on speaking skills were analyzed using descriptive and inferential statistics. Based on the analysis results, the average experimental group was 77.14 while the control group was 70.625 and (tcount = 2,682 >ttable = 1,68107). This research shows a significant effect of the talking stick learning model with mind mapping for speaking skills on fifth grade. Based on these findings, it can be concluded that the talking stick learning model with mind mapping affects speaking skills in fifth-grade students.